Association between 16S rRNA gene mutations and susceptibility to amikacin in Mycobacterium avium Complex and Mycobacterium abscessus clinical isolates - Kim, Su-Young (Sci Rep, 2021)
We evaluated the association between 16S rRNA gene (rrs) mutations and susceptibility in clinical isolates of amikacin-resistant nontuberculous mycobacteria (NTM) in NTM-pulmonary disease (PD) patients. Susceptibility was retested for 134 amikacin-resistant isolates (minimum inhibitory concentration [MIC] ≥ 64 µg/ml) from 86 patients. Amikacin resistance was reconfirmed in 102 NTM isolates from 62 patients with either Mycobacterium avium complex-PD (MAC-PD) (n = 54) or M. abscessus-PD (n = 8). MICs and rrs mutations were evaluated for 318 single colonies from these isolates. For the 54 MAC-PD patients, rrs mutations were present in 34 isolates (63%), comprising all 31 isolates with amikacin MICs ≥ 128 µg/ml, but only three of 23 isolates with an MIC = 64 µg/ml. For the eight M. abscessus-PD patients, all amikacin-resistant (MIC ≥ 64 µg/ml) isolates had rrs mutations. In amikacin-resistant isolates, the A1408G mutation (n = 29) was most common. Two novel mutations, C1496T and T1498A, were also identified. The culture conversion rate did not differ by amikacin MIC. Overall, all high-level and 13% (3/23) of low-level amikacin-resistant MAC isolates had rrs mutations whereas mutations were present in all amikacin-resistant M. abscessus isolates. These findings are valuable for managing MAC- and M. abscessus-PD and suggest the importance of phenotypic and genotypic susceptibility testing.